Space weather effects on Earth's environment associated to the 24–25 October 2011 geomagnetic storm. Issue 4 (8th April 2013) - Blanch, E.; Marsal, S.; Segarra, A.; Torta, J. M.; Altadill, D.; Curto, J. J.
Abstract : Space weather studies have increased due to human society dependence on spaceborne and terrestrial infrastructure vulnerable to its effects. In this paper, we present an interdisciplinary study of the effects of solar activity on the Earth's environment; specifically, we focus on the effects on the ionosphere and the geomagnetic field. A timeline of effects occurring on the Earth produced by one of the first relevant events of the present solar cycle (24–25 October 2011) is given. We have analyzed the solar wind shockwave from satellite data, the storm‐time development, the ionospheric effects at global and local scales using the National Center for Atmospheric Research Thermosphere‐Ionosphere‐Electrodynamics General Circulation Model fed with geomagnetic field‐aligned current data from the Active Magnetosphere and Planetary Electrodynamics Response Experiment, and ground ionosonde data from both hemispheres, at Ebre Observatory and Port Stanley locations. We have compared observed geomagnetic variations at high latitudes with those modeled by the National Center for Atmospheric Research Thermosphere‐Ionosphere‐Electrodynamics General Circulation Model. We have analyzed rapid geomagnetic variations (e.g., solar flare effect, storm commencement, Pi2) also on both hemispheres, at Ebre Observatory and Livingston Island locations. Finally, we have estimated geoelectric field and geomagnetically induced currents in the northeast of Spain (Catalonia) produced by this geomagnetic disturbance. Key Points: Interdisciplinary study of the solar activity effects on the Earth's environment Focused on the effects on the ionosphere and the geomagnetic field Timeline of effects occurred on 24‐25 October 2011 is given